The Father's Kenosis: A Defense of Bonaventure on Intra-trinitarian Acts. Issue 1 (February 2021) - Wood, Jordan Daniel
Russell Friedman identifies two "rival accounts" in medieval trinitarian theology. The "emanation account, " which Bonaventure represents, prefers to emphasize the constitutive role of "act" or "operation" among the intra-trinitarian persons. The "relation account, " that of Thomas Aquinas, prefers rather to say that relations alone constitute divine persons. A specific question illustrates their difference: Does the Father generate the Son because the Father is Father, or is He Father because He generates the Son? Aquinas thinks the former, Bonaventure the latter. Bonaventure's position attracts criticism from contemporary Thomists. And even Franciscan sympathizers have conceded ambiguity around this point of his trinitarian theology. To wit: If the Father's act of begetting the Son makes him Father, doesn't this presume a "Proto-Father, " as Friedman has it, who begets? I argue that this criticism ignores the uniquely Christian-Neoplatonic premises Bonaventure's view presumes. Perceiving them manifests Bonaventure's deep coherence on this point and beyond.